Enhancing panic and smoking reduction treatment with D-Cycloserine: A pilot randomized clinical trial. (1st March 2020) - Smits, Jasper A.J.; Zvolensky, Michael J.; Otto, Michael W.; Piper, Megan E.; Baird, Scarlett O.; Kauffman, Brooke Y.; Lee-Furman, Eunjung; Alavi, Noura; Dutcher, Christina D.; Papini, Santiago; Rosenfield, Benjamin; Rosenfield, David
Highlights: We tested if d -cycloserine (DCS) could reduce anxiety sensitivity and panic symptoms and thereby increase smoking abstinence. DCS facilitated greater reductions of one of the two mechanistic targets (anxiety sensitivity) which in turn predicted better smoking outcomes. There was no evidence of group (DCS vs. placebo) differences in smoking cessation success. Abstract: In this placebo-controlled randomized clinical trial, we examined the efficacy of 250 mg d -cycloserine (DCS) for enhancing the effects of cognitive behavior therapy targeting anxiety sensitivity reduction in the context of smoking cessation treatment among adults with a history of panic attacks. We hypothesized that DCS would enhance treatment of our mechanistic targets—anxiety sensitivity and panic and related symptoms—and result in greater smoking abstinence. A total of 53 smokers were randomized to a 7-week integrated treatment and received study medication (DCS or placebo) prior to sessions 3–5; these sessions emphasized interoceptive exposure practice. Nicotine replacement therapy was initiated at session 5 (quit date). We found that DCS augmentation led to greater reductions of one (anxiety sensitivity) of two of our mechanistic targets at early but not late assessments, and that engaging that target predicted better smoking outcomes. However, there was no evidence of group (DCS vs. placebo) differences in smoking cessation success at treatment endpoint or follow-up evaluations. Hence, although we found that DCS can enhance treatment targeting a smoking maintaining factor, additional strategies appear to be needed to significantly affect smoking outcomes.